Relationship between Travel Agents’ Service Quality and Tourists Satisfaction with Special Reference to Mirissa Coastal Tourism Zone - Jayampathi E.K.; Punchihewa P.S.D. (International Journal of Small and Medium Enterprises and Business Sustainability, 2019)
The complexity and globalization of today’s competitive business environment have made service quality as one of the most important sources of gaining competitive advantage in the tourism industry. Evaluation of customer satisfaction is one way to determine the service quality. Travel agents are one of key parties that engaged into the tourism sector to facilitate tourist in several means. Travel agents are to meet expectations and demands of tourist in accordance with quality of services which will be based on to retain existing and attract new tourists. In modern era, the quality of the services provided will be considered as the key factor that determining the survival of travel agencies in the market. This study focused on identifying the relationship between travel agents’ service quality and tourist satisfaction with especial reference to the Mirissa tourism zone, Sri Lanka. Population of this study was all the domestic and inbound tourists who visited Mirissa region during the period of 01st of March to 30th of March 2018. Sample of the study was consisted with 67 domestic and 133 inbound tourists who were visited to Mirissa tourism zone during the period of 01st of March to 30th of March 2018. Convenience sampling technique was used as the sampling technique and both primary and secondary data were used. Self-administered questionnaire was used to collect primary data. Correlation and Regression analytical techniques used to analyze data. This study concluded that there is a strong positive relationship between travel agents’ service quality and tourist satisfaction. Although, all dimensions in service quality were positively correlated, reliability was proven to have the most powerful positive impact on tourist satisfaction. Although, the study concluded that there is a strong positive relationship between travel agents’ service quality and tourist satisfaction, its better, if much awareness will be created on improving full-service web sites with new technologies for the convenience of selfserve online booking for tourists, as most of the tourists didn’t visit travel agencies in order to join with their service.